Building Connections with Families: Implementation of a Video-Messaging Service in the Neonatal Intensive Care Unit - Stephanie Bott; Nicole Dantas Fernandez; Janet Narciso; Janet MacAlpine; Nicole Quain; Julia Rettie; Lia Sharpe; Yenge Diambomba; Ayah Al Bizri; Karel O'Brien; Vibhuti Shah (MDPI AG, 2023)
Background: Family involvement is vital to optimize the care of infants in the neonatal intensive care unit (NICU). Various technologies have been used to support communication with parents in the NICU. The purpose of this study was to evaluate the parent and staff experience and perception of the use of a cloud-based video-messaging service in our NICU. Methods: This study was a single center observational study conducted at Mount Sinai Hospital, Toronto, Canada. Following the implementation of a video-messaging service, parent and staff surveys were distributed to evaluate their experience and perception. Results: Parent responses were positive with respect to how the service helped them feel: closer to their infant (100%) and reassured about their infant's care (100%). Nursing staff responses indicated that they perceived a benefit to parents (100%) and to their building a relationship with families (79%). However, they also identified time constraints (85%) and the use of the technology hardware (24%) as challenges. Conclusions: The use of an asynchronous video-messaging service was perceived as beneficial to both parents and staff in the NICU. Complaints pertained to the impact of the technology on nursing workflow and the difficulty using the hardware provided for use of the service.